A BiOCl nanodevice for pancreatic tumor imaging and mitochondria-targeted therapy. (October 2021) - Zhang, Xue-Hao; Guo, Ruo-Chen; Chen, Yuan-Fang; Xu, Xiao; Yang, Zi-Xin; Cheng, Dong-Bing; Chen, Hao; Qiao, Zeng-Ying; Wang, Hao
Highlights: Recognizing protein signal and targeting pancreatic cancer cell mitochondria. Photoacoustic imaging capability is obtained by introducing oxygen defects. Regulating oxygen vacancy defect and enhancing sonodynamic therapeutic effect. Graphical Abstract: ga1 Abstract: In cancer theranostics, it is of great significance to develop a hybrid material that can recognize and regulate physical and biological signals. Herein, a hybrid Bio-Signal Processor (BSP) is constructed by a BiOCl nanosheet, a semiconductor rich in oxygen vacancies (OVs), coated with two functional peptides. The BSP is capable of protein signal recognition, photoacoustic signal feedback and reactive oxygen species (ROS) output. The OVs-rich BiOCl with abundant active sites can generate ROS under excitation state. The BSP can specifically recognize plectin-1 protein of pancreatic cancer cells and feedback photoacoustic signals for tumor imaging. After further binding p32 protein on mitochondria, the BSP output ROS signals under ultrasound that destroyed mitochondria and kill cancer cells efficiently. Therefore, the BSP provide a new perspective for the development of intelligent chip for cancer theranostics.